The Digital Generation in Russian Education: from the Urgency of the Problem to Assessing the Impact of Digitalization on Students - S. V. Butsyk (Открытое образование (Москва))
The objectives of this research are: 1) an analysis of possible pedagogical strategies in relation to two age categories of Russian students (primary schoolchildren; older teenagers and youth) related to the new digital generation; 2) testing an experimental methodology for assessing the degree of influence of digitalization on the activities of older adolescents and youth on a relatively wide range of educational institutions (regular school, two different lyceums, institute) and for a relatively long period (two academic years).Materials and research methods are based on a number of foreign works in the field of pedagogy, psychology, neurophysiology, conducted in the USA, Great Britain, Singapore and a number of other countries, starting from the 2000s, as well as studies from the mid-2010s on the digital generation of Russia. The authors used the methodology for assessing the degree of influence of digitalization on students’ activities, previously published in the journal “Open Education” (No. 1/2019).Results of a study conducted during 2018 and 2019 in several schools of various types and a higher educational institution of one of the largest Russian regions allowed us to make an assumption about the noticeable significance of one of the two key indicators of the author’s methodology – “Significant Impact of Digitalization in the Activities of Students”. According to the author, it may indicate a lower or higher motivation of students in relation to educational and cognitive activities, including those resulting from the positive or negative impact of digitalization.Conclusion. The article describes two pedagogical strategies in relation to different age categories of students, aimed at increasing the motivation for using digital devices for educational and cognitive purposes. The first strategy is aimed at primary schoolchildren and was clearly demonstrated in the early 2000s at the Singapore Institute of Education. The second strategy, aimed at older adolescents and young people, requires the presence of certain social conditions and the consideration of a number of individual factors (average daily time of using digital devices; share of time using digital devices for educational and cognitive purposes; high-quality control of students’ parents or high self-control of students). Testing of the indicated experimental technique allowed the author to identify the boundary numerical values of these factors. At the same time, it is noted that the achievement of a slight negative impact of digital devices on the educational and cognitive activities of students does not require the complete fulfillment of absolutely all three of these factors.